2022
DOI: 10.1109/tcds.2021.3117925
|View full text |Cite
|
Sign up to set email alerts
|

Improving Synthetic to Realistic Semantic Segmentation With Parallel Generative Ensembles for Autonomous Urban Driving

Abstract: Semantic segmentation is paramount for autonomous vehicles to have a deeper understanding of the surrounding traffic environment and enhance safety. Deep neural networks (DNN) have achieved remarkable performances in semantic segmentation. However, training such a DNN requires a large amount of labelled data at pixel level. In practice, it is a labour-intensive task to manually annotate dense pixel-level labels. To tackle the problem associated with a small amount of labelled data, Deep Domain Adaptation (DDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…The advancement in deep learning has facilitated a better understanding of semantic representation and contributed to more accurate prediction of object locations. This line of research has a wide range of applications in autonomous driving (Ohn-Bar et al, 2020 ; Yi et al, 2021 ; Cao et al, 2022a ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement in deep learning has facilitated a better understanding of semantic representation and contributed to more accurate prediction of object locations. This line of research has a wide range of applications in autonomous driving (Ohn-Bar et al, 2020 ; Yi et al, 2021 ; Cao et al, 2022a ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being highly discriminative, semantic features extracted from deeper convolution layers are not suitable for representing small-sized/multi-class elements, which limits the accuracy of predicting multi-element BEV representations. Recent studies, including Yi et al ( 2021 ) and Yu et al ( 2021 ), have indicated that shallow feature maps are more effective for small-scale object detection as they provide rich spatial information. As a result, balancing the need for capturing large receptive field and extracting highly discriminative features can be challenging for CNNs.…”
Section: Introductionmentioning
confidence: 99%